1997
DOI: 10.1111/j.1365-2044.1997.006-az006.x
|View full text |Cite
|
Sign up to set email alerts
|

The minimum effective doses of pethidine and doxapram in the treatment of post‐anaesthetic shivering

Abstract: SummaryThis study was designed to find the minimum effective doses of doxapram and pethidine to stop post-anaesthetic shivering. Two hundred and twenty healthy patients who shivered following routine surgery were allocated randomly to receive one of 10 doses of doxapram (0.18, 0.23, 0.29, 0.35, 0.41, 0.47, 0.7, 0.93

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 8 publications
(15 reference statements)
1
51
1
2
Order By: Relevance
“…Earlier studies [4] have found that use of 1 mg/kg of Tramadol was associated with higher incidence of nausea and vomiting, and also sedation, which was not observed in our study. Some others [7] have suggested that slow injection of Tramadol over two minutes, reduces and prevents nausea and vomiting.…”
Section: Discussioncontrasting
confidence: 52%
“…Earlier studies [4] have found that use of 1 mg/kg of Tramadol was associated with higher incidence of nausea and vomiting, and also sedation, which was not observed in our study. Some others [7] have suggested that slow injection of Tramadol over two minutes, reduces and prevents nausea and vomiting.…”
Section: Discussioncontrasting
confidence: 52%
“…Nas situações em que a meperidina não pode ser usada os autores sugerem o uso de clonidina (150 µg), cetanserina (10 mg), alfentanil (0,25 mg) ou doxapram (100 mg). Deve ser lembrado que a manutenção da temperatura corporal intra-operatória e o uso de cobertores com ar aquecido no intra-e pós-operatório diminuem a necessidade de medicamentos para tratamento de tremores 76 . Em estudo realizado em 220 pacientes com o objetivo de identificar a dose eficaz de meperidina para o tratamento de tremores, Crossley 76 concluiu que 0,35 mg.kg -1 é a menor quantidade necessária para tratar tremor pós-operató-rio de forma satisfatória.…”
Section: Tratamento Dos Tremores Pós-operatóriosunclassified
“…Deve ser lembrado que a manutenção da temperatura corporal intra-operatória e o uso de cobertores com ar aquecido no intra-e pós-operatório diminuem a necessidade de medicamentos para tratamento de tremores 76 . Em estudo realizado em 220 pacientes com o objetivo de identificar a dose eficaz de meperidina para o tratamento de tremores, Crossley 76 concluiu que 0,35 mg.kg -1 é a menor quantidade necessária para tratar tremor pós-operató-rio de forma satisfatória. O uso do tramadol para tratamento de tremores tem sido feito nos últimos anos, e a sua eficácia é semelhante à da meperidina segundo alguns estudos 77 .…”
Section: Tratamento Dos Tremores Pós-operatóriosunclassified
See 1 more Smart Citation
“…tramadol 50mg i.v. Grading of shivering was done as per wrench [15] , which is as follows: Grade 0: No shivering, Grade 1: One or more of the following: Piloerection, Peripheral vasoconstriction, peripheral cyanosis with, but without visible muscle activity, Grade 2: Visible muscle activity confined to one muscle group, Grade 3: Visible muscle activity in more than one muscle group, Grade 4: Gross muscle activity involving the whole body. The study drug was administered slowly IV as per the allotted group.…”
Section: Preoperative Managementmentioning
confidence: 99%